PENGARUH KEMANDIRIAN BELAJAR, DISIPLIN BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP PERILAKU MENYONTEK MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Agus Fadrian; Agus Irianto (Program Magister Pendidikan Ekonomi (S2), 2015)
This research is aimed at finding out how far the influence of being autonomous in studying, descipline in studying, and motivation in get archievement on cheating behavior of economics student in State University of Padang.The type of this research is associative descriptive. The research is done in economics faculty of state university of padang. The population of this research is economics student in State university of Padang about 3.796 student. The sampling which is used 97 student with sratified sampling. The primery data of this research is collected by spreasing out the questionnaires to the sample or rrespondent of this research. The secondary data is the list of the student who can not follow the exam wich h is got by asking it directly to the academic section of Economics Faculty of State University of Padang. The collected data is analiyzed statistically with stripe analysis by using SPSS program version 16.00The result of the student concludes that (1) the autonomous in studying does not influence significantly on cheating behavior with the significances 0,738 > 0,05. (2) the desclipne in studying influences significantly on cheating behavior, with significances 0,021 < 0,05. (3) the motivation to get archievement influences significantly on cheating behavior, with significance 0,020 ,0,05. (4) the discipline in studying influences significantly on motivation to get archivement, with significance is 0,000 < 0,05. (5) the autonomous studying influences significantly on motivation to get archivement, with significance is 0,000 < 0,05.Based on the result of the research above, it can be concluded that influence of disclipne in studying and motivation to get archivement are the factors which can give the influence on autonomus in studying, discipline in studying and motivation to get archivement of economics student in State University of Padang. That is why, it is sugggested to the student of economic faculty of state University of Padang to Improve the discipline in studying and motivation to get archievement in order to omit the cheating behavior. Key Word : cheating behavior, motivation to get archievement, discipline in studying, and the autonomous in studying.